MODEL BELAJAR SANTRI DALAM KEARIFAN LOKAL DI PONDOK PESANTREN - Nur‘aini, Nur‘aini (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Islamic boarding schools are referred to as Islamic educational institutions because they are institutions that seek to instill Islamic values in the students. As an Islamic educational institution, pesantren have different characteristics compared to other educational institutions. This paper tries to describe efforts to develop student learning models in Islamic boarding schools. Pesantren which is synonymous with the yellow book in its work has a considerable influence on the Indonesian nation. The pesantren method always applies the values of local wisdom in traditional education patterns in the community. In Indonesia, there are many Islamic boarding schools that number in the thousands. In general, existing Islamic boarding schools apply traditional education patterns and modern education. However, although different patterns of educational learning patterns, they tend to have similarities in substance. One thing that seems inseparable from pesantren is that the santri learning model uses the yellow book as its study. There are several local moral values that can be upheld in pesantren that can be used as learning models that can be adopted by us in education today, one of which is a learning pattern that emphasizes the moral values of students. Such as: courtesy, discipline, example, patience and gratitude, cooperation, faith, responsibility